ANALYSIS OF THE INFLUENCE OF FLEXIBLE WORKING ARRANGEMENTS ON EMPLOYEE PERFORMANCE: THE ROLE OF WORK-LIFE BALANCE AND JOB SATISFACTION AS MEDIATING VARIABLES IN THE BANKING INDUSTRY - Didi Sutardi; Bayu Suseno; Rony Setiawan; Muhammad Nur Kasyfillah; Mazdhalifah Taro (JURNAL ILMIAH EDUNOMIKA, 2026)
Digital transformation and the dynamics of market demands in the modern era have forced the banking industry to reform conventional work systems towards more adaptive flexibility. This study aims to analyze the effect of Flexible Working Arrangements (FWA) on employee performance in the banking industry, by examining the mediating role of Work-Life Balance (WLB) and job satisfaction. Using a causal-associative quantitative design, primary data were collected through a structured 5-point Likert-scale questionnaire distributed to 320 bank employees who have adopted a flexible work system for at least the past year. The sampling method used non-probability purposive sampling, and data analysis was conducted using Structural Equation Modeling-Partial Least Squares (SEM-PLS) assisted by SmartPLS. The results of the analysis indicate that FWA has a positive and significant direct effect on employee performance. Furthermore, the structural analysis proves that Work-Life Balance and job satisfaction act as significant partial mediator variables in strengthening the relationship between FWA and employee performance. The highest total effect was found in the integrative path where FWA improves Work-Life Balance, which then stimulates job satisfaction, and ultimately results in a massive increase in employee performance. The practical implications of this study emphasize that banking industry management needs to design structured FWA regulations to optimize employee psychological balance in order to achieve organizational competitive advantage.